Enhancing Electron and Hole Extractions for Efficient PbS Quantum Dot Solar Cells. Issue 12 (8th November 2017) - Ren, Zhenwei; Kuang, Zhuoran; Zhang, Linlin; Sun, Jiankun; Yi, Xiaohui; Pan, Zhenxiao; Zhong, Xinhua; Hu, Jinsong; Xia, Andong; Wang, Jizheng
Abstract : Exploring ways capable of enhancing photocarrier extraction is crucial in further developing the current PbS quantum dots (QDs) solar cells with a standard architecture of ITO/ZnO/PbS‐TBAI/PbS‐EDT/Au, which are drawing enormous attention due to their high air stabilities and already achieved high power conversion efficiencies. Here, a thin layer of carbon QDs (CQDs) is employed to modify the ZnO film surface to improve photoelectron extraction, and a thin film of PbS QDs treated by a mixed ligand solution of EDT:CuI (PbS‐EDT:CuI) is used to replace the PbS‐EDT film to improve photohole extraction. This designed device (ITO/ZnO/CQDs/PbS‐TBAI/PbS‐EDT:CuI/Au) presents significantly improved PCE of 9.95% compared to 8.60% of the reference device (ITO/ZnO/PbS‐TBAI/PbS‐EDT/Au). In addition, the designed device shows very high air stability. Abstract : Carbon quantum dots (CQDs) and PbS‐EDT:CuI (PbS QDs treated by EDT:CuI solution) are integrated in PbS QDs solar cells to enhance electron extraction and hole extraction, respectively. This strategy significantly improves the power conversion efficiency to 9.95% from 8.60%. The designed device also shows very high air stability.